2017
DOI: 10.1080/00365513.2017.1397287
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension and high serum uric acid increase risk of arterial stiffness

Abstract: Prehypertension and serum uric acid are emerging as independent risk factors for arterial stiffness and may also predict cardiovascular diseases. Previous studies have demonstrated the association between serum uric acid and arterial stiffness in hypertensive adults, but there are limited studies in prehypertensive adults. We compared the serum uric acid (SUA) and cardio-ankle vascular index (CAVI) between normotensive and prehypertensive participants. The association between SUA, prehypertension and CAVI were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…Consistent with previous studies, 714 it was found that baPWV was positively correlated with uric acid levels in all subjects. In the regression analysis, various potential confounders were added in sequential order, but the results only revealed a modest reduction of effect (the regression coefficient changed from 0.31 to 0.28 after adjusting for a range of confounders), which strengthened the relationship between uric acid and baPWV.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies, 714 it was found that baPWV was positively correlated with uric acid levels in all subjects. In the regression analysis, various potential confounders were added in sequential order, but the results only revealed a modest reduction of effect (the regression coefficient changed from 0.31 to 0.28 after adjusting for a range of confounders), which strengthened the relationship between uric acid and baPWV.…”
Section: Discussionsupporting
confidence: 92%
“…These present results were in accordance with the recent case-control studies that focused on the causal relationship between uric acid and metabolic syndrome, and several cardiovascular diseases. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, conflicting results were still present. Parsa et al 21 reported that a decrease in serum uric acid has a causal effect of lowering blood pressure through the method of Mendelian randomization analysis in 516 Amish adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 In the present study, we found that BMI as an independent variable was inversely correlated with CAVI, which supports previous reports. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia was defined as total cholesterol ≥ 5.18 mmol/L, triglyceride ≥ 1.70 mmol/L, or LDL-C ≥ 3.37 mmol/L. Hyperuricemia was defined as blood uric acid > 420 μmol/L [26,27].…”
Section: Biochemical Testsmentioning
confidence: 99%